A genetic screen in Drosophila uncovers a role for senseless-2 in surface glia in the peripheral nervous system to regulate CNS morphology. - Lacin, H.; Zhu, Y.; DiPaola, J.T.; Wilson, B.A.; Zhu, Y.; Skeath, J.B. (G3 : genes - genomes - genetics, 2024)
Despite increasing in mass approximately 100-fold during larval life, the Drosophila CNS maintains its characteristic form. Dynamic interactions between the overlying basement membrane and underlying surface glia are known to regulate CNS structure in Drosophila, but the genes and pathways that establish and maintain CNS morphology during development remain poorly characterized. To identify genes that regulate CNS shape in Drosophila, we conducted an EMS-based, forward genetic screen of the second chromosome, uncovered 50 mutations that disrupt CNS structure, and mapped these alleles to 17 genes. Analysis of whole genome sequencing data wedded to genetic studies uncovered the affected gene for all but 1 mutation. Identified genes include well-characterized regulators of tissue shape, like LanB1, viking, and Collagen type IV alpha1, and previously characterized genes, such as Toll-2 and Rme-8, with no known role in regulating CNS structure. We also uncovered that papilin and C1GalTA likely act in the same pathway to regulate CNS structure and found that the fly homolog of a glucuronosyltransferase, B4GAT1/LARGE1, that regulates Dystroglycan function in mammals is required to maintain CNS shape in Drosophila. Finally, we show that the senseless-2 transcription factor is expressed and functions specifically in surface glia found on peripheral nerves but not in the CNS to govern CNS structure, identifying a gene that functionally subdivides a glial subtype along the peripheral-central axis. Future work on these genes should clarify the genetic mechanisms that ensure the homeostasis of CNS form during development.